Informal-formal linkages and informal enterprise performance in urban West Africa - Marcus Böhme; Rainer Thiele (Kiel Institute for the World Economy (IfW), 2012)
Employing a unique dataset that covers almost 6000 informal enterprises from six West African urban centers, this paper examines the backward and forward linkages of these enterprises to the formal sector. We first provide a descriptive analysis of the existing formal-informal linkages. It turns out that formal backward linkages are much more prevalent than formal forward linkages, and that linkages vary with the degree of informality, occurring less frequently if firms have no ties to the formal sector at all or low capital stocks. In the second step, we employ a Probit approach to identify major factors associated with the observed backward linkages. The Probit analysis corroborates the importance of the degree of informality for the existence of linkages and shows various enterprise characteristics to be significant determinants as well. Finally, we analyze whether backward linkages matter for enterprise performance using both OLS and IV estimations. We find a positive and robust impact of backward linkages, whereas the degree of informality of the enterprises in our sample seems to affect firm performance only indirectly through their linkages to the formal sector.
Keywords: D22; D40; O17; 330; informal sector; formal-informal linkages; enterprise performance; West Africa; Informeller Sektor; Lieferanten-Kunden-Beziehung; Dualökonomie; Unternehmensentwicklung; Stadt; Schätzung; Westafrika